Lower alpha fetoprotein and higher risk of hepatocellular carcinoma, study from the type 2 diabetes mellitus patients. (September 2018) - Yang, Shaoling; Liu, Lu; Luo, Yili; Chen, Ming; Li, Nan; Xu, Lu; Wang, Yanru; Lin, Ziwei; Li, Hong; Qu, Shen
Highlights: Diabetics had a lower geometric mean AFP level than non-diabetics. T2DM was associated with worse liver function and higher risk of high-grade HCC. Low AFP levels in diabetics might delay and/or interfere with HCC diagnosis. Abstract: Aims: To explore the association of type 2 diabetes mellitus (T2DM) with hepatocellular carcinoma (HCC) and alpha fetoprotein (AFP). Methods: 750 patients with T2DM (T2DM group), 800 healthy people (control group) and 501 patients newly diagnosed with HCC were recruited from 2010 to 2016. The HCC patients were further divided into a HCC with T2DM (HCC+DM) group and a HCC without diabetes mellitus (HCC+NDM) group. Results: The T2DM group had a 12.61% lower geometric mean AFP level than the healthy control group (2.08 vs. 2.38 μg/L, P < 0.001). Of 501 HCC patients, 230 (45.91%) had T2DM. When compared to the HCC+NDM group, the HCC+DM group had a higher negative rate of AFP (55.22% vs. 37.26%, P < 0.001), worse liver function ( P = 0.011) and a 64.87% lower geometric mean AFP level (25.71 vs. 73.18 μg/L, P < 0.001). T2DM was significantly associated with the risk of high-grade (grade 3 and 4) HCC (OR = 2.02, 95% CI 1.18–3.44, P = 0.010). Conclusions: T2DM was associated with lower AFP level, worse liver function and higher risk of high-grade HCC. We speculated that low AFP levels in diabetics might delay and interfere with HCC diagnosis, leading to higher degree of malignant HCC.